Log1/3(2x+1)-log1/3(2x+25)> 3+log1/3(x+2)

09365 09365    2   12.07.2019 21:10    3

Ответы
куллллл куллллл  30.08.2020 16:45
Log²(3)(x-1)-2log(-3)(9/(x-1)=7                 ODЗ x-1>0   x>1log²(3)(x-1)+2(log(3)(9)-log(3)(x-1))=7log²(3)(x-1)+2(2-log(3)(x-1))=7log²(3)(x-1)+4-2log(3)(x-1)-7=0log²(3)(x-1)-2log(3)(x-1)-3=0log(3)(x-1)=tt²-2t-3=0     D=4+12=16t1=(2+4)/2=3    t2=(2-4)/2=-1    log(3)(x-1)=3            log(3)(x-1)=-1                      x-1=3³   x-1=27    x=28                        x-1=1/3    x=4/3 
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра